Revolusi Pembelajaran dalam Matematika sebagai Konsekuensi dari Implementasi Physical Distancing - Rofi'ah, Faizatur (Jurnal VARIDIKA, 2020)
The proliferation of the corona virus affects all aspects of life, including education. This led to a revolution in the learning from conventional to digital. The purpose of this study is to 1) describe the general review of learning in mathematics and; 2) analyzing the alternatives to the learning revolution in mathematics with the physical policy of physical distancing. This research uses type of reference research. The validity test uses source data triangulation. Data validity obtained with various sources and extensions. Data analysis techniques use constant methods of comparison. The result of this article, which is 1) in general, math learning has been more conventional (face to face) and; 2) there is an alternative to math related to physical distancing, which is online/long-distance learning by making good use of accessible applications through Internet service. Online math learning by giving both a learning video, the settings are as interesting as possible, online discussions, and assessments through online quizzes.